Nigeria : 2017 Article IV Consultation- Press Release; Staff Report; and Statement by the Executive Director for Nigeria. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights low oil prices' and falling oil production's blow to the Nigerian economy. The country entered a recession in 2016, with growth contracting by 1.5 percent. Annual inflation doubled to 18.6 percent, reflecting higher electricity costs and fuel tariffs, a weaker naira, and accommodating monetary conditions. Even with significantly lower capital spending, the consolidated fiscal deficit increased from 3.5 percent of GDP in 2015 to 4.7 percent of GDP in 2016. Under unchanged policies, the outlook remains challenging and growth would pick up only slightly to 0.8 percent in 2017, mostly reflecting some recovery in oil production and a continuing strong performance in agriculture.